2020
DOI: 10.24200/jonus.vol5iss2pp329-364
|View full text |Cite
|
Sign up to set email alerts
|

Power and Solidarity in Positive Facebook Postings Amidst Covid-19 in Malaysia

Abstract: Background and Purpose: Coronavirus has posed an unfamiliar threat to the world. Despite such circumstances, Malaysians continue to stay optimistic by keeping abreast with updates and mostly by seeking refuge in hopeful and consoling messages shared by fellow citizens. This study identified Facebook postings with positive messages, posted by Malaysians during the Movement Control Order (MCO) implemented by the Malaysian government as a form of prosocial behaviour.   Methodology: Through an analytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 25 publications
0
20
0
8
Order By: Relevance
“…Of note, the Malaysian government has taken serious action on misleading information related to COVID-19 posted on social media. A study by Azizan et al ( 42 ) demonstrated that Malaysians expressed their solidarity and empowerment to fight the crisis on Facebook during the outbreak. This implies the positive effects given by social media to Malaysians in handling the unprecedented event.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the Malaysian government has taken serious action on misleading information related to COVID-19 posted on social media. A study by Azizan et al ( 42 ) demonstrated that Malaysians expressed their solidarity and empowerment to fight the crisis on Facebook during the outbreak. This implies the positive effects given by social media to Malaysians in handling the unprecedented event.…”
Section: Discussionmentioning
confidence: 99%
“…The PDA study on the pandemic discourse shows that there is an effort to foster power and solidarity among citizens. The findings from Azizan et al (2020) show that through Facebook posts, citizens support each other by using the pronoun "we", collective expressions, or advice. The study emphasized the role of a strong sense of togetherness and solidarity, a strong national identity, values of patriotism and religion to unite and to fight the pandemic.…”
Section: The Covid-19 Pandemic Discourse and Public Anxietymentioning
confidence: 99%
“…In addition, studies on the Covid-19 discourse emphasized the individual and institutional efforts to build spirit through communication during the Covid-19 pandemic (Azizan et al, 2020;Jinshuang & Rong, 2020). By studying Facebook posts about critical situations during the pandemic, Azizan et al (2020) reported four positive themes expressed by the Malaysians that include religion, patriotism, call for heroism and public awareness. The study also revealed that linguistic strategies such as speech acts and figurative language contribute to creating public's positive reactions.…”
Section: Introductionmentioning
confidence: 99%
“…In Malaysia, social media is used by Malaysians during the COVID-19 pandemic as the platform to show their sense of togetherness through the proliferation of positive messages ( Azizan et al, 2020 ). Social media has become the place to brighten up each other’s spirit.…”
Section: Introductionmentioning
confidence: 99%